2021
DOI: 10.20452/pamw.15886
|View full text |Cite
|
Sign up to set email alerts
|

Radial approach reduces mortality in ST-segment elevation myocardial infarction with cardiogenic shock

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…[26][27][28] In present study, we found no significant impact of chronic renal dysfunction or creatinine on LOS. Interestingly, although numerous studies proved more advantages of transradial approach than transfemoral access in percutaneous coronary intervention (PCI), 29 even for STEMI patients with cardiogenic shock, 30 transradial approach was not an independent associated factor of LOS in this analysis. This result might reflect serious LOS redundancy in a different way.…”
Section: Discussionmentioning
confidence: 57%
“…[26][27][28] In present study, we found no significant impact of chronic renal dysfunction or creatinine on LOS. Interestingly, although numerous studies proved more advantages of transradial approach than transfemoral access in percutaneous coronary intervention (PCI), 29 even for STEMI patients with cardiogenic shock, 30 transradial approach was not an independent associated factor of LOS in this analysis. This result might reflect serious LOS redundancy in a different way.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, the confounding factors of the procedure time should be controlled for in further investigations. A previous study 39 suggested that the radial approach was associated with lower periprocedural mortality than the femoral approach in 3565 consecutive patients with MI. The radial approach appears to be a worthwhile option in technical situations.…”
Section: Discussionmentioning
confidence: 93%
“…A comprehensive delineation of the ORPKI national registry was demonstrated in previous analyses [15][16][17][18]. In brief, this registry provides evidence of all PCI procedures performed in Poland since 2004.…”
Section: Methodsmentioning
confidence: 90%